Establishment Of a Safavid State in Iran - Nimat Shahab Haji; Khalil Ali Murad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The establishment of the Safavid state in the year 1501 on the hands of the Shah Ismail the First (1501-1722) is considered one of the most important stages in the history of Iran, given the early beginning of the formation of this new state and its independence from foreign powers, especially the Mongols and Ilkhanade empires, who had already occupied Iran in two stages, one after the other. Although some researchers believe that they belonged to the Safavid family, which did establish a national state in Iran, there is little evidence to support this view. However, we can say that the arrival of the Safavid family, the national identity begun within the boundaries of the newly established state, it is important to remember that it did not reach national security, until a new state was created. In the aftermath of this discussion, we have tried to shed light on the foundations of the Safavid family and the reasons for their emergence and development, as well as the way in which they came to power. In this regard, the study seeks to highlight the important aspects of religious, social, political, military, and even important areas under the control of the Safavid family. With the highlight of the important reasons behind the steps taken by Sheikh Ismail, the son of Sheikh Haider, to establish an independent state in one of the most complex and turbulent regions of Azerbaijan in early sixteenth-century Iran.